Exploiting embryonic niche conditions to grow Wilms tumor blastema in culture - Wojcik, Heather M.; Lovvorn, Harold N.; Hollingshead, Melinda; Pierce, Janene; Stotler, Howard; Murphy, Andrew J.; Borgel, Suzanne; Phelps, Hannah M.; Correa, Hernan; Perantoni, Alan O. (Frontiers in Oncology, 2023)
Wilms Tumor (WT), or nephroblastoma, is the most common pediatric kidney cancer. Most WTs display a “favorable” triphasic histology, in which the tumor is comprised of blastemal, stromal, and epithelial cell types. Blastemal predominance after neoadjuvant chemotherapy or diffuse anaplasia (“unfavorable” histology; 5-8%) portend a worse prognosis. Blastema likely provide the putative cancer stem cells (CSCs), which retain molecular and histologic features characteristic of nephron progenitor cells (NPCs), within WTs. NPCs arise in the metanephric mesenchyme (MM) and populate the cap mesenchyme (CM) in the developing kidney. WT blastemal cells, like NPCs, similarly express markers, SIX2 and CITED1. Tumor xenotransplantation is currently the only dependable method to propagate tumor tissue for research or therapeutic screening, since efforts to culture tumors in vitro as monolayers have invariably failed. Therefore, a critical need exists to propagate WT stem cells rapidly and efficiently for high-throughput, real-time drug screening. Previously, our lab developed niche conditions that support the propagation of murine NPCs in culture. By applying similar conditions to WTs, we have successfully expanded and passaged WT cells from five distinct untreated patient tumors and maintained key NPC “stemness” markers, SIX2, NCAM and YAP1, and CSC marker ALDH1. These findings suggest that our culture conditions sustain the WT blastemal population, as previously shown for normal NPCs. As a result, we have developed new WT cell lines and a multi-passage in vitro model for studying the blastemal lineage/CSCs in WTs. Furthermore, this system supports growth of heterogeneous WT cells, upon which potential drug therapies could be tested for efficacy and resistance.